QUALITY OF LIFE, LEVEL OF ANXIETY AND LEVEL OF DEPRESSION AMONG FORMER ARTISTIC GYMNASTS, FORMER GYMNASTS FROM OTHER SPORTS AND NONATHLETES - Dimitriadou, Koralli; Dallas, Costas; Papouliakos, Sotiris; Dallas, George (Science of gymnastics journal, 2022)
Abstract Involving people in physical activity or sport provides some health-related benefits and has a positive effect on their quality of life (QoL). [...]former gymnasts, even after years of absence from the sport, report better QoL, and have a lower level of STAI and BDI than non-athletes. Exercise includes physical movements, but this form of physical activity is programmed and specially designed to be repeated in order to improve or maintain the physical condition of the individual (Zourikian et al., 2012; World Health Organization, 2019). According to Filbay, Pandya, Thomas, McKay, Adams, and Arden (2019), QoL of former athletes is less understood and there is a possibility that sport has a positive or even negative effect on their later life.